Soluções viáveis para utilização do Pure Data no desenvolvimento de audiogames mobile para pessoas com deficiência visual na plataforma Unity - Lima, Ramon Paulino de (2021)
The mobile games segment represents a relevant part of the industry, moving billions of dollars every year, due to its popularity and easy access in everyday life. Unfortunately a large portion of users are out of this type of media, the VI (visually impaired), and for this audio-based games (or audiogames) emerge to meet this need. The aim of this study is to investigate the use of Pure Data (Pd) in the development of mobile audiogames on the Unity platform. To do this, we developed Binaural Flight, an endless vertical scrolling game exploring the integration of Pure Data and the Unity platform. In the course of this work we verified that Pd is viable and versatile as a real-time audio manipulation and generation tool in the game. The use of libpd allows the implementation of Pd on several platforms. From this study, we propose a set of solutions to assist in the use and implementation of Pure Data in the development of mobile audio games on the Unity platform, thus making it a viable option for independent developers and thus fostering new audio game productions for visually impaired individuals.